Clinical Significance of Pim-1 in Human Cancers: A Meta-analysis of Association with Prognosis and Clinicopathological Characteristics. (30th May 2022) - Lai, Lin; Chen, Xinyu; Tian, Ge; Liang, Renba; Chen, Xishan; Qin, Yuelan; Chen, Kaihua; Zhu, Xiaodong
Background: Pim-1 is overexpressed in cancer tissues and plays a vital role in carcinogenesis. However, its clinical significance in cancers is not fully verified by meta-analysis, especially in relation to prognosis and clinicopathological features. Methods: Four databases, PubMed, Embase, Cochrane Library, and Web of Science, were searched. Literature screening and data extraction according to the inclusion and exclusion criteria. The quality of the included literatures was evaluated using the Newcastle-Ottawa scale and the data analysis was performed using STATA and Review Manager software. Results: 15 articles were finally included for meta-analysis, involving 1651 patients. Effect-size pooling analysis showed that high Pim-1 was related to poor overall survival (OS) (HR 1.68 [95% CI 1.17-2.40], P = .004) and disease-free survival (DFS) (HR 2.15 [95 %CI 1.15-4.01], P = .000). Subgroup analysis indicated that the detection techniques of Pim-1 were the main sources of heterogeneity, and 2 literatures using quantitative polymerase chain reaction (qPCR) for Pim-1mRNA had high homogeneity (I 2 = .0%, P = .321) in OS. Another 13 studies that applied immunohistochemistry (IHC) for Pim-1 protein had significant heterogeneity (I 2 =82.2%, P = .000; I 2 =92%, P = .000) in OS and DFS, respectively, and further analysis demonstrated that ethnicity, sample size, and histopathological origin were considered to be the main factors affecting their heterogeneity. In addition, high Pim-1 was associated with lymph node metastasis (OR 1.40 [95% CI 1.02-1.92], P = .04), distant metastasis (OR 2.69 [95%CI 1.67-4.35], P < .0001), and clinical stage III-IV (OR .7 [95% CI .50-.96, P = .03). Sensitivity analysis suggested that the pooled results of each effect-size were stable and reliable, and there was no significant publication bias ( P = .138) in all included articles. Conclusion: High Pim-1 can not only predict poor OS and DFS of cancer, but also help to infer the malignant clinical characteristics of tumor metastasis. Pim-1 may be a potential and promising biomarker for early diagnosis, prognostic analysis and targeted therapy of tumors.